Paleotectonic Setting of Cambro-Ordovician Volcanic Rocks in the Canadian Appalachians - Fyffe, L.; Swinden, H. (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1991)
Abstract Recent advances in the understanding of petrogenetic processes at plate boundaries, coupled with improved trace-element and geochronological analytical techniques, permit a more sophisticated approach to paleo-geographic reconstructions of ancient volcanic environments. This paper reviews published geochemical data on Cambro-Ordovician volcanic rocks of the Canadian Appalachians and uses these data to interpret the plate tectonic setting of the volcanic activity. Synthesis of the data suggests that some spatial relationships among the various volcanic suites may have been maintained with respect to the Laurentian and Avalonian continental margins despite considerable crustal shortening across, and transcurrent displacement parallel to, the Appalachian Orogen. Six tectono volcanic environments are recognized, including passive-margin rift volcanic rocks, oceanic island volcanic rocks, sub-arc ophiolltes, island-arc volcanic rocks, back-arc ophiolltes, and continental-margin back-arc volcanic rocks. Passive-margin, rift-related volcanic rocks include Late Precambrian to Early Cambrian, within-plate, tholeiitic to transition alalkalic basalts and associated per alkaline rhyolites of the Sutton Mountains in Québec and the Cloud Mountain and Deer Lakeare as of Newfoundland. These volcanic rocks were extruded onto Grenville crustalong the northwestern margin of the Appalachian Orogen and, together with the Late Precambrian Long Range dyke swarm, indicate that a period of crustal extension, related to the formation of an ancient oceanbasin, persisted for at least 60 million years. Sub-arc ophiolltes include Early Ordovician ophiolite complexes from the Eastern Townships of Québec and Baie Verte Peninsula of northwestern Newfoundland. The presence of boninites and primitive-arc volcanic rocks suggests that these ophiolltes represent the foundation to arc systems rather than ocean floor generated at a mid-oceanic ridge. Volcanic-arc suites in central Newfoundland range from Late Cambrian to Early Ordovician in age and commonly varyin composition from primitive-arc tholeiites to mature-arc, calc-alkaline volcanic rocks inthe lower parts, to rocks similar to ocean floor and ocean island basalts in the upper parts of the successions. This variation ingeochemistry suggests a change in tectonicenvironment from long-established subduc-tion-related to back-arc-related volcanism. Early Ordovician ophiolite complexes inparts of central Newfoundland contain volcanic rocks with ocean floor geochemical characteristics and are believed to have been generated in back-arc basins. An ophiolite complex in northern New Brunswick, which is some 20 million years younger than those in Newfoundland, contains volcanic rocks that are transitional between ocean floor and island-arc basalts — a feature typical of many back-arc oceanic settings. Early Ordovician volcanic rocks in northwestern New Brunswick possess a mature-arc character, but do not appear to record a period of back-arc development; non-arc volcanic rocks are, however, a bundant inadjacent areas of Maine. Volcanic rocks in central and northern New Brunswick and in southern Newfoundland are dominated by Early Ordovician, silica-rich felsic flows and tuffs that are intercalated with, and overlain by, Early to Late Ordovician mafic volcanic rocks ranging in composition from continental tholeiites to within-plate alkali basalts.These bimodal suites are interpreted to havef ormed within back-arc basins underlain bysialic crust of possible Avalonian affinity.